Adsorption of B(α)P on carbon nanopowder affects accumulation and toxicity in zebrafish (Danio rerio) embryos. Issue 5 (5th April 2017) - Della Torre, Camilla; Parolini, Marco; Del Giacco, Luca; Ghilardi, Anna; Ascagni, Miriam; Santo, Nadia; Maggioni, Daniela; Magni, Stefano; Madaschi, Laura; Prosperi, Laura; La Porta, Caterina; Binelli, Andrea
Abstract : The interactions of nanomaterials with contaminants represent great concern for the environment and human health. Abstract : The increasing use of nanomaterials raises several concerns regarding their potential risk for the environment and human health. In particular, the aquatic ecosystems appear highly susceptible. In this context, we investigated the interplay between carbon nanopowder (CNPW) and the common pollutant benzo(α)pyrene (B(α)P) in zebrafish embryos. CNPW was contaminated with B(α)P, and showed significant adsorption towards the hydrocarbon. Embryos were then exposed to CNPW (50 mg L −1 ) or B(α)P (0.2, 6, 20 μg L −1 ) alone, or to the CNPW doped with the three B(α)P concentrations. We demonstrated that CNPW helps B(α)P uptake by zebrafish embryos and we also demonstrated that the interaction between CNPW and the hydrocarbon affects the stress response pathways of the organism, so eliciting the toxic effect. In particular, the modulation of genes related to the cellular stress response ( cyp1a, hsp70, sod1, sod2 ) and the measurement of oxidative stress enzyme activities allowed us to identify critical molecular events modulated by the pollutants alone and in co-exposure. Finally, to evaluate the toxic effects due to CNPW interactions with B(α)P, we analyzed biomarkers of cyto-genotoxicity. No significant genotoxicity was induced by B(α)P and CNPW alone, but the co-exposure led to an increase of cytotoxicity, and a higher incidence of necrotic and apoptotic cells. Altogether our data show that nanomaterials, even if they are not toxic per se, could help to enhance the toxicity of common pollutants.